Disability training for health workers: a global evidence synthesis - Rotenberg, S; Rodríguez Gatta, D; Wahedi, A; Loo, R; McFadden, E; Ryan, S (Elsevier, 2022)
Background Health worker training on disability is a recognized component of achieving high standards of health for people with disabilities, given that health worker’s lack of knowledge, stigma, and negative attitudes towards people with disabilities act as barriers to high quality health care. Objective To understand the published literature on training health workers about disability. Methods We searched five databases for relevant peer-reviewed articles published between January 2012 and January 2021. Studies that focused on training health care workers to improve knowledge, confidence, self-efficacy, and competence to support people with physical, sensory, or intellectual impairments were included. Data about the details of the intervention (setting, participants, format, impact assessments, etc.) and its effects were extracted. Results There is an array of highly local tools to train health workers across stages of their training and careers (preservice, in-service, and continuing professional development). Studies involving people with disabilities in the training, community placements, simulations, or interactive sessions were found to be most effective in improving knowledge, confidence, competency, and self-efficacy. Conclusions As part of initiatives to build inclusive health systems and improve health outcomes for people with disabilities, health workers around the world need to receive appropriate and evidence-based training that combines multiple methods and involves people with disabilities. To monitor progress on the impact of training, there should also be a standardized measure of impact on core outcomes.